If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3r + r + 25 + -6 = 11 + 2 + -7 Reorder the terms: 25 + -6 + 3r + r = 11 + 2 + -7 Combine like terms: 25 + -6 = 19 19 + 3r + r = 11 + 2 + -7 Combine like terms: 3r + r = 4r 19 + 4r = 11 + 2 + -7 Combine like terms: 11 + 2 = 13 19 + 4r = 13 + -7 Combine like terms: 13 + -7 = 6 19 + 4r = 6 Solving 19 + 4r = 6 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + 4r = 6 + -19 Combine like terms: 19 + -19 = 0 0 + 4r = 6 + -19 4r = 6 + -19 Combine like terms: 6 + -19 = -13 4r = -13 Divide each side by '4'. r = -3.25 Simplifying r = -3.25
| 3X+2=-7X-7 | | x+(13+x)+(-29+3*x)=599 | | 3X+2=-7X+7 | | 6(2z-1)-3(z+7)=4(2+1) | | -6A+2+7A=13-25 | | 4x-32=y | | 3Q-18=4Q+14+10 | | x-6(8x+6)=5-47x | | 4X+6=7-3 | | -2/3*4=x | | 7p-5(p-q)-p= | | -2/3*4= | | log(8x+11)=2 | | 2x+3=3x+20 | | 7x+2(x-5)=4 | | 5X+6+4X=3-6 | | 10(x+2)-4(2x+1)=2(x+6) | | E^9x=5.9 | | F(x)=-x^2+8x+7 | | 9n+2n-5=-60 | | 8(a+2)=72 | | F(x)=-x^2-6x+5 | | 3x-4+5x+20=180 | | 3x-4+5x+20=360 | | 5=log(x+1) | | 8+5(x-7)=8-4(x-8) | | 5X-7X+X=4-2X | | 5e+2.5=2.5-7.5c | | -5.5+3.5(1-9.5k)=25.5 | | 0.24x+3.8x=-2.02 | | 8+5x-35x=8-4x-32 | | 4(2b-3x)=7b+5x |